(untitled) - Schmitt, Norbert (Cambridge, 2000)
This text offers a comprehensive introduction to vocabulary for language teachers who would like to know more about the way vocabulary works. It provides the background knowledge necessary for practitioners to make informed choices about vocabulary teaching and testing. The overall theme is making research and theory accessible, and then drawing on it to suggest effective classroom applications
Keywords: Language and languages,Vocabulary; Study and teaching